Natural variations of growth thermo‐responsiveness determined by SAUR26/27/28 proteins in Arabidopsis thaliana. Issue 1 (26th June 2019) - Wang, Zhixue; Yang, Leiyun; Liu, Zhenhua; Lu, Minghui; Wang, Minghui; Sun, Qi; Lan, Yiheng; Shi, Tieliu; Wu, Dianxing; Hua, Jian
Summary: How diversity in growth thermo‐responsiveness is generated for local adaptation is a long‐standing biological question. We investigated molecular genetic basis of natural variations in thermo‐responsiveness of plant architecture in Arabidopsis thaliana . We measured the extent of rosette architecture at 22°C and 28°C in a set of 69 natural accessions and determined their thermo‐responsiveness of plant architecture. A genome‐wide association study was performed to identify major loci for variations in thermo‐responsiveness. The SAUR 26 subfamily, a new subfamily of SAUR genes, was identified as a major locus for the thermo‐responsive architecture variations. The expression of SAUR26/27/28 is modulated by temperature and PIF4. Extensive natural polymorphisms in these genes affect their RNA expression levels and protein activities and influence the thermo‐responsiveness of plant architecture. In addition, the SAUR26 subfamily genes exhibit a high variation frequency and their variations are associated with the local temperature climate. This study reveals that the SAUR26 subfamily is a key variation for thermo‐responsive architecture and suggests a preference for generating diversity for local adaptation through signaling connectors.